2019
DOI: 10.1002/aelm.201900012
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Ferroelectricity, and Magnetism in Self‐Assembled BiFeO3–CoFe2O4 Nanocomposites on (110)‐LaAlO3 Substrates

Abstract: grow as a tetragonal structure with a large c/a ratio (≈1.25) when the compressive epitaxial strain exceeds ≈4.5%, e.g., when grown on LaAlO 3 (LAO). [29] In previous work on BFO-CFO nanocomposites, (001)-oriented pseudocubic substrates were typically used, and there is little work on nanocomposites grown with (110) and (111) orientations. [21,31,32] The CFO nanopillars in nanocomposites grown on (110) and (111) substrates appear as tent-like structures and triangular prisms, respectively, in contrast to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 42 publications
(62 reference statements)
1
15
1
Order By: Relevance
“…47 Meanwhile, advanced probe microscopes have been employed to directly observe and verify these phase/polarization distributions (with/without fields) of each domain at the micron/nanoscale. [48][49][50] It has been reported that the pillar size plays a critical role in controlling ME coupling in BTO-CFO VANs as it is determined by the competition between the vertical interface coupling effect and the bulk volume conservation effect. 51,52 Moreover, experiments have also been widely performed to improve the phase distribution morphologies and to enhance the properties of ME VANs.…”
Section: Understanding What Controls Me Vans and Rich Approaches To Adjustments Via Film Growthmentioning
confidence: 99%
“…47 Meanwhile, advanced probe microscopes have been employed to directly observe and verify these phase/polarization distributions (with/without fields) of each domain at the micron/nanoscale. [48][49][50] It has been reported that the pillar size plays a critical role in controlling ME coupling in BTO-CFO VANs as it is determined by the competition between the vertical interface coupling effect and the bulk volume conservation effect. 51,52 Moreover, experiments have also been widely performed to improve the phase distribution morphologies and to enhance the properties of ME VANs.…”
Section: Understanding What Controls Me Vans and Rich Approaches To Adjustments Via Film Growthmentioning
confidence: 99%
“…[34][35][36] Doing so, BFO structure and properties can be widely modified, adapting and designing the material to different situations/use/working conditions and recent works have been focused on BFO A-site doping. BFO systems have been deposited on various substrates using pulsed laser deposition (PLD), [37,38] metal organic chemical vapor deposition (MOCVD), [39][40][41][42][43] sputtering, [44] sol-gel, [45,46] and chemical solution deposition. [38,47] In this study, we report on the promising pyroelectric properties of pure BFO and Dy-doped BFO (BDFO) films deposited, through a simple, easily scalable MOCVD approach, on Nb doped SrTiO 3 (STO:Nb) (001) single crystal substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Piezoresponse force microscopy (PFM) is an essential tool for studying ferroelectric properties of such systems with nanoscale spatial variations. [1,2,[4][5][6][7][8][9]14,[16][17][18][19][20][21]38,39,43,44] For ferroelectric switching of BFO-CFO VAN systems, however, only one or a few local hysteresis loops are typically measured, usually by "parking" a conductive atomic force microscopy (AFM) probe at single or arrayed points in BFO, sweeping the tip-sample bias, and recording the resulting changes in the piezoresponse. [2,4,11,[15][16][17][18]28,38] Single-point hysteresis measurements can be challenging to interpret, though, due to the superposition of piezoelectric effects and electrostatics [45] or ionic motion.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2,[4][5][6][7][8][9]14,[16][17][18][19][20][21]38,39,43,44] For ferroelectric switching of BFO-CFO VAN systems, however, only one or a few local hysteresis loops are typically measured, usually by "parking" a conductive atomic force microscopy (AFM) probe at single or arrayed points in BFO, sweeping the tip-sample bias, and recording the resulting changes in the piezoresponse. [2,4,11,[15][16][17][18]28,38] Single-point hysteresis measurements can be challenging to interpret, though, due to the superposition of piezoelectric effects and electrostatics [45] or ionic motion. [46] Topographic crosstalk is another persistent concern due to sensitivities to the tip-sample contact area, especially when the surface morphology exhibits changes in slope or curvature with length scales equivalent to the dimensions of the tip apex.…”
Section: Introductionmentioning
confidence: 99%